Dampak Peraturan Daerah Terkait Kesehatan terhadap Prevalensi Stunting Tingkat Kabupaten/Kota di Indonesia - Putra, Cakra Yudi; Dartanto, Teguh (Jurnal Ekonomi dan Pembangunan Indonesia, 2026)
Stunting remains a major public health challenge in Indonesia with long-term impacts on health, cognition, and productivity. This study examines whether health-related regional regulations (Peraturan Daerah or Perda) reduce stunting prevalence across 338 districts/municipalities in 2007 and 2013. Using Difference-in-Differences (DiD) and DiD with Propensity Score Matching (DiD-PSM) on secondary data from Riskesdas, Statistics Indonesia (BPS), and the Legal Documentation and Information Network (JDIH), we find no statistically significant causal effect of cumulative health Perda on stunting reduction, although OLS shows a negative association. Sanitation significantly reduces stunting in eastern Indonesia. Findings highlight the need for evidence-based, multisectoral, measurable, implementable, and evaluated health regional regulations.